ChemInform Abstract: Catalytic Three‐Component One‐Pot Reaction of Hydrazones, Dihaloarenes, and Amines. Issue 20 (25th April 2013) - Roche, Maxime; Hamze, Abdallah; Brion, Jean‐Daniel; Alami, Mouad
Abstract The present new method allows efficient sequential C—C bond formation and intermolecular C—N cross‐coupling to afford 1, 2‐diaryl ethylene derivatives of biological interest.